Sandler enterprise selling : winning, growing, and retaining major accounts - Mattson, David, 1963-; Sullivan, Brian W. (McGraw-Hill, 2016)
Providing the framework needed to succeed in the enterprise arena; to win; grow; and keep major accounts; this practical; step-by-step book demonstrates how; to keep treasured clients and gain new ones; you need a system to win business with profitable enterprise clients; serve them effectively and grow the relationships over time. --